ANALYSIS OF FACTORS AFFECTING INVESTMENT DECISIONS - Komang Onik Putriani; I Gede Sanica (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to determine the effect of investment experience, risk tolerance, technological developments, personal income, financial behavior and investment decisions. The population of this study are all investors who are domiciled in Denpasar City and Badung Regency with a total sample of 165 respondents. The data processing technique used is the Structural Equation Model (SEM) with Smart PLS software. The research results show that the variables of investment experience, risk tolerance, personal income and financial behavior have a direct and significant effect on investment decisions. While the variable technological progress has no significant effect on investment decisions. The investment experience variable has an indirect effect through the risk tolerance variable and the personal income variable has an indirect effect through the financial behavior variable on investment decisions.